2012
DOI: 10.1007/s00705-012-1236-8
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation analysis of the E2 gene of human papilloma virus type 16 in cervical lesions from women in Greece

Abstract: The E2 gene of human papilloma virus is expressed at the early stage of the viral life cycle, encoding the E2 transcription factor, and regulates the expression of E6 and E7 oncogenes. Disruption of E2 gene due to viral integration inhibits the transcriptional suppression of the HPV oncogenes, inducing cell proliferation. In the present study, a total of 22 HPV16-positive cytological specimens derived from high- and low-grade cervical intraepithelial lesions were investigated in order to identify sequence vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Three of these were OPSCCs and two were non-OPSCC. Of the three OPSCC samples, all three involved deletions within the hinge region, which has been reported to harbor deletions in cervical cancer [ 50 52 ]. Deletions within the hinge region may hinder nuclear localization of E2 and E2-dependent replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these were OPSCCs and two were non-OPSCC. Of the three OPSCC samples, all three involved deletions within the hinge region, which has been reported to harbor deletions in cervical cancer [ 50 52 ]. Deletions within the hinge region may hinder nuclear localization of E2 and E2-dependent replication.…”
Section: Discussionmentioning
confidence: 99%
“…Among the two non-OPSCC tumors, one harbored a deletion in the hinge region and the other a deletion in the transactivation domain. However these E2 sequences were identified as being non-functional due to mutations within the E2 gene (Genebank IDs HM162463.1 and HM162476.1) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were incubated at 37 ο C overnight, and proteinase K was inactivated at 95 ο C for 15 min. The lysate was removed by a brief spin, and the resulting supernatant was transferred into a new tube [Tsakogiannis et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies investigated the physical state of HPV16 genome through mapping of disrupted sites in E1 and E2 ORFs [Kalantari et al, 1998;Lukaszuk et al, 2003;Arias-Pulido et al, 2006;Cricca et al, 2009]. Interestingly, disruption of E2 gene was associated with high grade cervical malignancies [Arias-Pulido et al, 2006;Cricca et al, 2009;Tsakogiannis et al, 2012]. A previous study by Cricca et al [2009] reported that disruption of both E1 and E2 genes occurred in high grade cervical intraepithelial malignancies whereas in low grade cases only E1 gene disruption was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Such mechanisms include the methtylation status of HPV DNA (Refs 146, 152, 153) or mutations into the viral genome that change the protein functions of the E2 and E6 proteins and subsequently augmented the viral capacity to transform the epithelium. Such mutations have been described at position 3240 (E2, C3410T) (Refs 154, 155) as well as at position 350 (E6, T350G) (Refs 156, 157, 158).…”
Section: Integration Of Hpv Dnamentioning
confidence: 99%